2021
DOI: 10.1177/11297298211008103
|View full text |Cite
|
Sign up to set email alerts
|

Use of cyanoacrylate glue for the sutureless securement of epicutaneo-caval catheters in neonates

Abstract: Introduction: Epicutaneo-caval catheters (ECC) are pivotal for drug and fluid infusion in neonates. Given the intrinsic importance of the catheter for the patients’ health and the need to avoid stressful and painful procedures on premature or critically ill newborns with fragile and poor vein asset, it is clearly necessary an accurate bundle for ECC insertion and management to avoid complications that may lead to non-elective ECC removal. Among others, dislodgment is an acknowledged complication, and conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 14 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…The use of medical cyanoacrylate glue is proposed to be superior to conventional dressing in reducing the incidence of catheter dislocation (31). Also, we suggest that at any time, should a chest radiograph be performed for any clinical purpose, the neonatal Displacement of PICC inserted through the Basilic vein during arm movement.…”
Section: Discussionmentioning
confidence: 99%
“…The use of medical cyanoacrylate glue is proposed to be superior to conventional dressing in reducing the incidence of catheter dislocation (31). Also, we suggest that at any time, should a chest radiograph be performed for any clinical purpose, the neonatal Displacement of PICC inserted through the Basilic vein during arm movement.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their safety, biocompatibility, effectiveness, flexibility, and better cosmetic effect, the use of CSCAs in neonatal and pediatric populations has recently gained increasingly more attention of clinicians and health care providers. In 2021, D'Andrea et al52 published the use of cyanoacrylate TAs for the sutureless securement of epicutaneo-caval catheters in neonates. The study concluded that the addition of CSCAs to conventional securement methods was effective in reducing accidental dislodgement of epicutaneo-caval catheters and limiting bleeding and oozing at the puncture site and that CSCAs were easy and safe to use, which may be an effective antimicrobial mechanical barrier 52.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, D'Andrea et al52 published the use of cyanoacrylate TAs for the sutureless securement of epicutaneo-caval catheters in neonates. The study concluded that the addition of CSCAs to conventional securement methods was effective in reducing accidental dislodgement of epicutaneo-caval catheters and limiting bleeding and oozing at the puncture site and that CSCAs were easy and safe to use, which may be an effective antimicrobial mechanical barrier 52. In order to minimize CR-BSIs in critically ill children, Biasucci et al44 evaluated the effectiveness of a bundle that includes use of CSCAs to seal and protect catheter incision sites and demonstrated a decrease in CR-BSI rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FDA has stated that TA may be used safely with both infants and premature neonates, and also with chlorhexidine-sensitive patients. The benefit is that the adhesive can be applied to a very small surface area, in addition to that occupied by the catheter, allowing for fine adjustments of the catheter in any securement position 22–25. During the time of dressing changes and/or device removal, a silicone-based adhesive remover is used to prevent unwanted medical adhesive-related skin injuries (MARSIs).…”
Section: Definitionmentioning
confidence: 99%